Gas production prediction and risk quantification of shale gas reservoirs in Sichuan Basin based on Gauss prediction model and Monte Carlo probability method - Li, Haitao; Yu, Guo; Fang, Yizhu; Chen, Yanru; Wang, Chongyang; Zhang, Dongming (Frontiers in Earth Science, 2022)
The shale gas exploration and development potential in the Sichuan Basin is huge. Production prediction and risk quantification are important in planning of natural gas resources. Hubbert and Gauss models are used to predict the growth trend of production in the gas reservoir. Based on the prediction results, the Monte Carlo simulation is used to calculate the probability of production realization. The evaluation matrix of risk level is established by using indices of production realization probability and dispersion degree for assessing the risk level of shale gas production. The results show that: 1) when URR is at the same growth rate, Gauss model has a more stable yield growth trend than Hubbert model, and the correlation coefficients of Gauss model are all higher than that of Hubbert model. This means that the production prediction results of the Gauss model have higher accuracy. 2) According to the Gauss model, the shale gas will reach peak production of (280–460) × 108 m3/a in 2042 and will have stable production from 2037 to 2047. By the end of the stable production stage, the URR exploitation degree is about 60%; 3) The Monte Carlo method can be used to obtain the production realization probability for each year. The risk level evaluation matrix can be established by taking the probability of realization and the dispersion degree as evaluation indices, which can provide the systematization of the risk levels. This study is helpful to deepen the understanding of natural gas exploration and development. And it is of great significance to gas field development planning and production index realization.